Strategies to Promote Solidarity among High School Students through History Learning - Novita Mujiyati (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Social solidarity is an attitude of camaraderie, respect, differences acceptance andawareness of shared goals as a member of society. It must be increased among high schoolstudents. Accordingly, the study of history has a strategic role to promote social solidarityamong them. The method used in this research is qualitative descriptive. Based on theresearch results, the solidarity of students can be improved through the implementation ofpopular resistance against foreign rule in the 19th centuryvalues -based historylearning.Keywords:Students’ solidarity, history learning,